2021
DOI: 10.1007/s00170-021-07158-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acoustic excitation on fiber-reinforced polypropylene and the influence on melt viscosity

Abstract: The paper describes a novel technological approach to influencing the rheological properties of thermoplastic materials exposed to acoustic energy. The flow behavior of polypropylene with different mass percentages of glass fibers is investigated in a parallel plate rheometer under high-frequency longitudinal excitation. The influence of oscillation frequency on the melt viscosity is explained by means of shear thinning criteria. The dependence of the oscillation shape using sinusoidal excitation on shear thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Another possible explanation for the varying thickness reduction in the samples with constant frequency could be due to a higher matrix viscosity compared to the samples with varying frequency. Higher frequencies could lead to a higher excitement of the molecular chains and thus reducing the London dispersion forces, which reduces the matrix viscosity [78]. Moreover, a shift in frequency could also leads to a shift in wavelength, which could result in a better absorption of the energy emitted from the light source by the molecules.…”
Section: Micrographsmentioning
confidence: 99%
“…Another possible explanation for the varying thickness reduction in the samples with constant frequency could be due to a higher matrix viscosity compared to the samples with varying frequency. Higher frequencies could lead to a higher excitement of the molecular chains and thus reducing the London dispersion forces, which reduces the matrix viscosity [78]. Moreover, a shift in frequency could also leads to a shift in wavelength, which could result in a better absorption of the energy emitted from the light source by the molecules.…”
Section: Micrographsmentioning
confidence: 99%
“…In studies devoted to the rheology of polymers [34][35][36][37][38], it is indicated that the vibration excitation application, in the process of casting polymers, significantly reduces the viscosity of the polymer composition, in some cases [36] up to 9.6 times. However, these studies relate to thermoplastic polymers, and additional studies are required for thermosets.…”
Section: Metal-polymer Rheology In Mold Channelsmentioning
confidence: 99%